2011
DOI: 10.1080/10705422.2011.595306
|View full text |Cite
|
Sign up to set email alerts
|

Upper Middle Class NIMBY in Phoenix: The Community Dynamics of the Development Process in the Arcadia Neighborhood

Abstract: This article highlights the role that neighborhood activism plays in the development process. The article particularly highlights the Arcadia Camelback Neighborhood Association's (ACMNA) fight against, and collaboration with, developers at the intersection of 44th Street and Camelback Road in Phoenix, AZ, where issues of place, community empowerment, and attitudes of not-in-my-backyard (NIMBYism) played out. The role of neighborhood activism is evaluated using interview, survey, and archival data, including ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Purcell (2006) argues that the literature about local governance tends to assume that the local is preferable to other scales without sufficient evidence to support this belief—which he terms the “local trap.” Fainstein (2010), while in general supportive of the local governance scale, clarifies that although local knowledge is important and likely contributes to more democratic decision-making, the planning outcomes may not necessarily be more equitable due to public participation alone. A classic example of how the local scale might interfere with larger societal interests is the not-in-my-backyard (NIMBY) phenomenon, where residents and/or associations object to the placement of facilities or services in proximity to their homes, despite the facilities’ benefits to the wider community (see Buckman 2011; Schively 2007). In many cases, NIMBYism is carried out by relatively privileged and wealthy residents who have the time and means to promote their agenda, which may disregard the needs of less privileged ones.…”
Section: The Role Of Ncs In Participatory Urban Governancementioning
confidence: 99%
“…Purcell (2006) argues that the literature about local governance tends to assume that the local is preferable to other scales without sufficient evidence to support this belief—which he terms the “local trap.” Fainstein (2010), while in general supportive of the local governance scale, clarifies that although local knowledge is important and likely contributes to more democratic decision-making, the planning outcomes may not necessarily be more equitable due to public participation alone. A classic example of how the local scale might interfere with larger societal interests is the not-in-my-backyard (NIMBY) phenomenon, where residents and/or associations object to the placement of facilities or services in proximity to their homes, despite the facilities’ benefits to the wider community (see Buckman 2011; Schively 2007). In many cases, NIMBYism is carried out by relatively privileged and wealthy residents who have the time and means to promote their agenda, which may disregard the needs of less privileged ones.…”
Section: The Role Of Ncs In Participatory Urban Governancementioning
confidence: 99%
“…The socioeconomic influences on substantive agenda setting are important inasmuch as local participatory entities such as CROs have drawn criticism for channeling middle-class prerogatives and engaging in NIMBYistic opposition to social services and affordable housing (Buckman 2011;Hiner and Galt 2011;Lyon-Callo 2001;Oakley 2002;Pendall 1999;Segal, Baumohl, and Moyles 1980;Zippay and Lee 2008). This literature supports several hypotheses regarding the relationship between SES and agenda, under the assumption that socioeconomic influences will differ for operational activities and substantive policy engagement.…”
Section: Socioeconomic Influences On Neighborhood Agenda Settingmentioning
confidence: 99%
“…Consistent with this observation, Pendall’s (1999) study of 182 proposed housing development projects in the San Francisco metropolitan region finds that NIMBY-oriented objections were typically framed in terms of concerns over traffic, property values, or privacy, and only rarely in explicitly racial or near-racial terms. And Buckman’s (2011) case study of NIMBY objections to new housing and retail development in an upper-income Phoenix neighborhood finds that the debate was framed in terms of neighborhood character or sense of place rather than in clearly racial or income-class terms. On the other hand, in their content analysis of newspaper coverage of affordable housing development in California, Nguyen, Basolo, and Tiwari (2013) found that NIMBY attitudes were generally framed, explicitly or implicitly, in terms of the expected race or ethnicity and income class of those expected to occupy that housing.…”
Section: An Exit Voice and Loyalty Model Of Neighborhood Changementioning
confidence: 99%